2003
DOI: 10.1080/1360786021000006956
|View full text |Cite
|
Sign up to set email alerts
|

The COPE index--a first stage assessment of negative impact, positive value and quality of support of caregiving in informal carers of older people

Abstract: Data was collected in five countries from informal carers of older people (n = 577) via a common protocol. Carers completed: (1) a 17-item version of the Carers of Older People in Europe (COPE) Index, an assessment of carers' perceptions of their role : (2) a questionnaire on demographic and caregiving circumstances : and (3) three instruments included for the criterion validation of the COPE Index (the General Health Questionnaire, the Hospital Anxiety and Depression Scale, and the World Health Organization Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
108
0
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 30 publications
0
108
0
16
Order By: Relevance
“…l Positive aspects of caring These were measured using the four-item positive aspects subscale from the Carers of Older People in Europe (COPE) index. 157 Responses are recorded from the categories never, sometimes, often and always (or not applicable). l Personal growth The 3-item version Personal Growth Index was used.…”
Section: Peer Support and Joint Reminiscence For People With Dementiamentioning
confidence: 99%
“…l Positive aspects of caring These were measured using the four-item positive aspects subscale from the Carers of Older People in Europe (COPE) index. 157 Responses are recorded from the categories never, sometimes, often and always (or not applicable). l Personal growth The 3-item version Personal Growth Index was used.…”
Section: Peer Support and Joint Reminiscence For People With Dementiamentioning
confidence: 99%
“…Measures developed in other contexts, e.g. family function in a paediatric setting [39], for economic evaluation [40], domain-specific measures [41] and multidimensional measures which have not been subject to psychometric evaluation in cancer caregivers in the English language [6,42,43] may include concepts and items that are pertinent but which would need to be evaluated in appropriate studies.…”
Section: Limitationsmentioning
confidence: 99%
“…Criterion validity tests among family caregivers of older people 21,23 and caregivers of older persons with dementia 31 have shown that overall the subscales correlate satisfactorily with the chosen criteria. The test score reliability in terms of internal consistency (Cronbach's alpha) has previously been examined in populations of family caregivers of older people 23 , caregivers of older homecare clients (not including clients with cancer, dementia or psychiatric disorders) 25 and caregivers of disabled people.…”
mentioning
confidence: 99%
“…20 Nevertheless, the instrument was designed to be a first-stage assessment tool, and more detailed assessments and dialogs with caregivers are warranted to adapt interventions to individual needs. 23 The psychometric properties of the original 2003 COPE Index 21 were sub-optimal; hence, a revised version was adopted in 2006 in a six-country European survey of family caregivers of older people (EUROFAMCARE study). 23 An exploratory factor analysis revealed that the following three components underpinned the 15 items: negative impact of caregiving, positive values of caregiving and quality of support.…”
mentioning
confidence: 99%
See 1 more Smart Citation